2021
DOI: 10.1007/s11214-021-00800-3
|View full text |Cite
|
Sign up to set email alerts
|

Gravity, Geodesy and Fundamental Physics with BepiColombo’s MORE Investigation

Abstract: The Mercury Orbiter Radio Science Experiment (MORE) of the ESA mission BepiColombo will provide an accurate estimation of Mercury’s gravity field and rotational state, improved tests of general relativity, and a novel deep space navigation system. The key experimental setup entails a highly stable, multi-frequency radio link in X and Ka band, enabling two-way range rate measurements of 3 micron/s at nearly all solar elongation angles. In addition, a high chip rate, pseudo-noise ranging system has already been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 68 publications
0
30
0
Order By: Relevance
“…As a final remark, we outline an approach to extend GRAPE for practical mission planning and compatibility with NASA's SPICE kernels (Acton 1997). This will be formally addressed in a future manuscript and we expect the important results of the Cassini-Huygens (Bertotti et al 2003) and BepiColumbo (Serra et al 2018;Iess et al 2021) radioscience experiments to serve as important verification tests for future versions of GRAPE. When complete, GRAPE will utilise the PN IAU operational-ready spacetime metrics for both geocentric and barycentric studies and will calculate important light-time observables ) associated with interplanetary probes.…”
Section: Grape: First Results and Discussionmentioning
confidence: 96%
“…As a final remark, we outline an approach to extend GRAPE for practical mission planning and compatibility with NASA's SPICE kernels (Acton 1997). This will be formally addressed in a future manuscript and we expect the important results of the Cassini-Huygens (Bertotti et al 2003) and BepiColumbo (Serra et al 2018;Iess et al 2021) radioscience experiments to serve as important verification tests for future versions of GRAPE. When complete, GRAPE will utilise the PN IAU operational-ready spacetime metrics for both geocentric and barycentric studies and will calculate important light-time observables ) associated with interplanetary probes.…”
Section: Grape: First Results and Discussionmentioning
confidence: 96%
“…Further details concerning the gravimetry and rotation experiments can be found in Cicalò et al (2016), and Schettino et al (2017), while an extensive analysis of the the relativity experiment is presented in and Schettino et al (2018). Moreover, a comprehensive review of the MORE experiment has been recently published in Iess et al (2021).…”
Section: Simulation Setup and Nominal Resultsmentioning
confidence: 99%
“…The only official instrument onboard BepiColombo that was originally planned to be operating during cruise was the Mercury Orbiter Radio science Experiment (MORE, Iess et al, 2021) during superior solar conjunctions. Nevertheless, the beginning of the cruise phase has revealed that other instruments on board Mio and MPO could be operating as well and exploited for scientific studies.…”
Section: Operational Instruments Science Topics and Constraintsmentioning
confidence: 99%
“…These include the detection of Gamma-Ray Bursts (GRBs) and their localization, in particular the gamma-rays that originate from solar flares, and monitoring the local radiation background of the spacecraft due to bombardment by energetic particles of Galactic Cosmic Rays. Last but not least, 7) General relativity test could be performed during superior solar conjunctions (e.g., Bertotti et al, 1993;Iess et al, 2021). Two major constraints had to be taken into account for the planning of the joint observations with BepiColombo.…”
Section: Operational Instruments Science Topics and Constraintsmentioning
confidence: 99%